The Effect Of Work Motivation And Position Promotion On Employee Performance At The West Lampung Regency DPRD Secretariat - Ruhiyat, Yayat; Sodirin, Sodirin (Universitas Dehasen Bengkulu, 2025)
The process of moving an employee to a higher position is called promotion. This study aims to identify three factors that influence employee performance at the West Lampung Regency DPRD Secretariat, namely: 1. motivation to work and the effect of job promotion on employee performance; and 2. the combined effect of work motivation and job promotion on employee performance.The purpose of this descriptive quantitative research is to identify the relationship between variables in the population. This research does so using numerical data. Simple and multiple regressions were used. The study involved 35 people participating. The results of data analysis show the answers to the following hypotheses: Work Motivation (X1) affects performance (Y) at the DPRD Secretariat, with an influence level (R-square) of 72.5%; Position Promotion affects performance at the DPRD Secretariat, with an influence level of 62.2%; and both affect employee performance at the DPRD Secretariat of West Lampung Regency, with an influence level of 62.2%